2006
DOI: 10.1074/jbc.m602135200
|View full text |Cite
|
Sign up to set email alerts
|

An Iron-induced Nitric Oxide Burst Precedes Ubiquitin-dependent Protein Degradation for Arabidopsis AtFer1 Ferritin Gene Expression

Abstract: Ferritins play an essential role in iron homeostasis by sequestering iron in a bioavailable and non-toxic form. In plants, ferritin mRNAs are highly and quickly accumulated in response to iron overload. Such accumulation leads to a subsequent ferritin protein synthesis and iron storage, thus avoiding oxidative stress to take place. By combining pharmacological and imaging approaches in an Arabidopsis cell culture system, we have identified several elements in the signal transduction pathway leading to the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(117 citation statements)
references
References 82 publications
5
112
0
Order By: Relevance
“…In line with this, ferritin mRNAs are also strongly accumulated in response to iron overload in vascular plants (Arnaud et al, 2006;Lescure et al, 1991;Petit et al, 2001b).…”
Section: Discussionmentioning
confidence: 49%
“…In line with this, ferritin mRNAs are also strongly accumulated in response to iron overload in vascular plants (Arnaud et al, 2006;Lescure et al, 1991;Petit et al, 2001b).…”
Section: Discussionmentioning
confidence: 49%
“…Treatment with a specific NOS inhibitor reduced NO levels in elicited control plants but not in silenced lines, confirming an involvement of NOS1 in the observed NO burst (Asai et al, 2008). Other reports, however, found that NO accumulation in response to different hormones or oxidative stress was similar in nos1 and wild-type plants (Arnaud et al, 2006;Kolbert et al, 2008;Tun et al, 2008). Impaired NO generation in mutant plants in response to some treatments but not in response to others has been observed even under similar experimental conditions.…”
Section: First Leads In the Hunt For Plant Nos Enzymesmentioning
confidence: 66%
“…Nonenzymatic production of NO from nitrite involving the plastidial pigments carotenoids has also been reported (Cooney et al, 1994). Interestingly, NO synthesis in response to iron, elicitors, high temperatures, salinity, or osmotic stress is first detected in chloroplasts using NO-sensitive diaminofluorescein probes (Foissner et al, 2000;Gould et al, 2003;Arnaud et al, 2006). Although many pieces of the puzzle are still missing, and the search for the elusive plant NOS is not yet over, these results corroborate the hypothesis that plastids are key players for the control of NO levels in plant cells.…”
Section: A Role For Plastids In the Control Of No Levelsmentioning
confidence: 99%
“…A large cavity that occupies about 30% of the total protein volume at the center of the cage is the mineralization site of ferritin ferrihydrite. The importance of ferritin is illustrated by embryonic lethality of gene deletion in mammals (1) and resistance to oxidants in animals, plants, bacteria, and archea that reflects consumption of iron(II) and dioxygen or hydrogen peroxide (2)(3)(4)(5). Some classes of nanomaterials use ferritin nanocages as templates (6).…”
mentioning
confidence: 99%